Surface characterization of thin liquid layers on a solid substrate upon heating - Li, Weichi. (2013)
This project to build an experimental set-up to observe the convection cells formed from a thin layer of a viscous liquid when heated from bottom and to study how different parameters could affect the formation and visualization of the convection cells.